Hubungan Internasional tentang Kerjasama Kemanusiaan Negara Utara dan Negara Selatan (Indonesia dan Australia) - Yeyen Subandi (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2016)
The southern states can be regarded as a developing country views of the average income is low, infrastructure that can be said is still relatively underdeveloped, and also the human development index which is less than the northern countries as the developed countries. Here the exception of Australia and New Zealand, despite being located in the southern part, but both countries have been classified into developed countries. Relation to humanitarian cooperation between Australia and Indonesia has been going on for a long time, and this partnership is experiencing bright and dim influenced by the political situation and international relations between the two countries. Leadership change affect the existing cooperation, because both countries still need each other in bilateral relations, although sometimes intervention. The purpose of this study was to see whether the assistance provided by Australia solely for humanitarian or any other purpose. In this article will use qualitative methods and results can be informed or to sharing for students, non-governmental organizations (NGO) and government who have been getting foreign aid from Australia in humanitarian issues, until now the Indonesian government still expect and rely on the Australian government about assistance or cooperation in humanitarian issues.